A study of the production system of Allied Concrete Products Incorporated - Gutano, Georgina D. (College of Engineering, 2002)
The study aims to identify the major problems of the company in the area od production and operations management. The group intends to recommend alternative actions to address the problems affecting the company's production system to enable it to function more efficiently and effectively and allow it to face the combined pressure of fierce competition and rapidly changing market demands. The company under study, Allied Concrete Products Inc. is a pipe and block company serving the Central and Southern Luzon market. The company manufactures concrete pipes, modular and decorative blocks, as well as pre-cast concrete manhole systems. The group decided to focus on the concrete pipes product line since they are produced on a regular basis. Summary of findings from the examination of this product line was used as an indicator of te company's system of operations as a whole. The group conducted plant visits and personnel interviews to gather information on the operations of the company and identify its concerns with regards to production/operations management. The group utilized the streamline diagnostic chart the group focused on the problem of lack of formal (qualitative) forecasting technique, no medium-term plan production plan and warehousing problem (finished goods). To determine the appropriate demand forecasting technique, the group gathered demand data for the years 1999-2001. For the products with no seasonal demand patterns, the weighted moving average and exponential smoothing with alpha= 0.2 and 0.5, were considered, respectively. Based on the evaluations of the tracking signals, the group recommends that the company make use of the exponential smoothing method with alpha 0.5 to forecast the future demand of pipes with sizes 12, 15, 18,21,24 and 48. The multiplicative seasonal method is suggested as the as the appropriate technique to forecast the demand volume of concrete pipes sizes 30, 36, and 42". From the forecasted demands, the group evaluated the use of the Level and the Chase strategy as possible aggregate planing strategy. Based on the cost calculations performed, the group recommends that the company utilize a mixed strategy of keeping 13 workers at the minimum to produce demanded on a regular basis (make-to-stock products), hiring more workers when there are large orders of make to order pipes and firing workers when the demand for these pipes decrease. In addressing the warehousing problem of finished goods, the group considered alternative production-stock are assignment with the aim of minimizing the materials handling effort exerted in transporting pipes from one place to another. From the evaluation of the alternatives considered, the group has found out that the implementation of a new pipe size-production area and production-stock area assignment (Refer to Figure 17) yields a reduction in the in the material handling effort from 34505.05 down to 23404.00. Aside fom the reduction in the material handling effort, implementation of this new assignment scheme may also facilitate the flow of materials within the production plant and stockpiling of finished goods.